REVIEW ARTIKEL STUDI FITOKIMIA DAN FARMAKOLOGI TEMU PUTIH (Curcuma zedoaria) - Yuyun Rahmawati; Arista Wahyu Ningsih; Irvan Charles; Retha Amalia Rahma Dewi; Fina Agustin; Salsabilla Rohadatul A; Ervina Aryani (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2023)
Indonesia, which is rich in biodiversity, is very much in harmony with the culture or habits of the people who still uphold hereditary values, especially in terms of herbal (traditional) medicine. Utilization of medicinal plants in Indonesia has begun to develop rapidly, where medicinal plants used can be used directly or through an extraction process to obtain compounds that have pharmacological and therapeutic effects. One of the medicinal plants that is often used by the Indonesian people is a type of rhizome that includes ginger, yellow turmeric, white ginger, ginger, and many more. One of the rhizomes that are efficacious for health is white ginger (Curcuma zedoaria). In the test white ginger extract (Curcuma zedoaria) was positive for the presence of flavonoids, alkaloids, tannins and saponins, curcumin. These compounds that make Temu Putih (Curcuma zedoaria) have pharmacological activities including antioxidant, anti-inflammatory, anticancer, antibacterial, as an immunodulator, anti-angiogenic and can act as an antitumor.